Influenza vaccination coverage of healthcare workers and residents and their determinants in nursing homes for elderly people in France: a cross-sectional survey - Guthmann Jean-Paul; Fonteneau Laure; Noël Delphine; Vaux Sophie; Lévy-Bruhl Daniel (BMC, 2010)
Abstract Background Nursing home residents bear a substantial burden of influenza morbidity and mortality. Vaccination of residents and healthcare workers (HCWs) is the main strategy for prevention. Despite recommendations, influenza vaccination coverage among HCWs remains generally low. Methods During the 2007-2008 influenza season, we conducted a nationwide survey to estimate influenza vaccination coverage of HCWs and residents in nursing homes for elderly people in France and to identify determinants of vaccination rates. Multivariate analysis were performed with a negative binomial regression. Results Influenza vaccination coverage rates were 33.6% (95% CI: 31.9-35.4) for HCWs and 91% (95% CI: 90-92) for residents. Influenza vaccination uptake of HCWs varied by occupational category. Higher vaccination coverage was found in private elderly care residences, when free vaccination was offered (RR: 1.89, 1.35-2.64), in small nursing homes (RR: 1.54, 1.31-1.81) and when training sessions and staff meetings on influenza were organized (RR: 1.20, 1.11-1.29). The analysis by occupational category showed that some determinants were shared by all categories of professionals (type of nursing homes, organization of training and staff meetings on influenza). Higher influenza vaccination coverage was found when free vaccination was offered to recreational, cleaning, administrative staff, nurses and nurse assistants, but not for physicians. Conclusions This nationwide study assessed for the first time the rate of influenza vaccination among residents and HCWs in nursing homes for elderly in France. Better communication on the current recommendations regarding influenza vaccination is needed to increase compliance of HCWs. Vaccination programmes should include free vaccination and education campaigns targeting in priority nurses and nurse assistants.